Subordinate Clause Functioning as an Adjunct in Complex Sentences Found in Online Newspaper - Yohanes Candrasius; Putu Devi Maharani (LPPM Universitas Bumigora Mataram, 2024)
The aim of this research is to analyze the subordinate clause functioning as an adjunct in complex sentences found in online CNN newspapers. This research method is qualitative. The data for this study were collected using the observation method. To analyze the data found, the descriptive qualitative method was used. This study used the theory proposed by Aarts (2001) to examine the subordinate clause functioning as an adjunct in a complex sentence. Meanwhile, the constituent structure of the three diagrams is analyzed using the theory proposed by Kroeger (2005). The data analysis in this study was delivered through formal and informal methods. The results of this research are 18 data functioning as adjuncts from 16 Articles posted on 10&11 August 2023. Among these 18 subordinate clauses functioning as an adjunct, 10 were linked with adverbial time or 55.55%, 4 were connected with adverbial reason or 22.22% 3 were linked with the adverbial condition or 16.66%, and 1 was linked with adverbial concession or 5.55%. The implication of this study is the students learn subordinate clauses functioning as an adjunct in complex sentences through online media.